An outbreak of H7N6 low pathogenic avian influenza in quails in Japan - Katsuaki Sugiura; Keiji Fushimi; Tomoyuki Takehisa; Masuji Miwa; Takehiko Saito; Yuko Uchida; Takashi Onodera (Veterinaria Italiana, 2009)
In February and March 2009, a total of seven quail farms in the Aichi Prefecture in Japan were found to be infected with an avian influenza (AI) virus. Low pathogenic AI viruses, subtype H7N6, were isolated from three of these farms. The infection was eliminated through the destruction of susceptible birds on the infected premises, movement controls of quail and other poultry in areas around infected premises, accompanied by intensive clinical, serological and virological surveillance. Sentinel quails were used to verify that the infected farms were free from AI virus before they were restocked. An epidemiological study revealed that the virus was likely to have been introduced into the infected area some time ago. Economic losses amounted to 874 million yen (US$9.75 million), mainly accounting for costs incurred by control and eradication measures and financial support for the infected farms and farms in the movement control areas.